Does Exchange Rate Regime, Political Stability, and Capital Controls Influence the Currency Crisis - llah, Zia U; Fen, Tan Xiao; Tunio, Fayaz Husain; llah, Imran U (The journal of contemporary issues in business and government, 2021)
This study used the probit models to examine the relationship between exchange rate regime, political stability, and capital controls on currency crises. Dataset is based on 1996 to 2020 over the currency crisis episodes in 23 high-income countries and 25 middle-income countries, and the total observation annually is 1200. Recent empirical studies have mixed results and argue that the relationship is expected to depend on capital controls and political stability both with the exchange rate. The analysis provides impressive results for fixed exchange rate and capital controls are negatively associated with crisis, significantly less stable governments. The results strongly support that floating exchange rate and (open) economies are negatively associated with crises and lower the risk of crisis, remarkably more stable political governments. (Open) economies and floating exchange rates are positively associated with a currency crisis and more prone to a currency crisis, exceptionally less stable political governments.